IMPLEMENTASI PENGGUNAAN MEDIA GAMBAR TERHADAP MINAT BELAJAR PADA MATA PELAJARAN IPS KELAS IV SD INPRES 9 DURIANKARI KABUPATEN SORONG - Souisa, Haryo Franky; Dailom, Katerina; Tutuarima, Natalya (LPPM Politeknik Saint Paul Sorong, 2025)
This research investigates the implementation of picture media in Social Studies (IPS) learning for fourth-grade students at SD Inpres 9 Duriankari, Sorong Regency. The study employed a qualitative approach with field research methods to describe the implementation and its effect on students' learning interest. Data was collected through observation, interviews, and questionnaires. The findings reveal that the use of picture media was systematically planned and implemented, aligning with effective media utilization principles. Picture media effectively visualized abstract concepts, increased student engagement, and positively influenced learning motivation and focus. The integration of picture media with varied teaching methods is recommended to optimize the learning process. Keywords : Picture Media, Learning Interest, Social Studies, Elementary School, Sorong Regency